Identifikasi Wilayah Rawan Banjir Genangan Menggunakan Teknologi Sistem Imformasi Geografis (SIG) (Studi Kasus : Kota Pekanbaru) - Wikrine Teriyoko; Mudjiatko Mudjiatko; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Stages of disaster mitigation study consists of the level of hazard, vulnerability and capacity. Pekanbaru, the capital of Riau province has the potential to flood inundation. An assessment of the vulnerability of flood inundation using GIS technology be done in twelve districts in the city of Pekanbaru. This study was conducted as a early warning to the public and to the relevant parties. This study uses two parameters causes of flood inundation, such as the parameter of flooding inundation (landform, slope either side of the river, damming the river branching, meandering rivers, and waterworks) and parameters of flood inundation potential water supply (rainfall, river basin shape, drainage density, slope watersheds, and land use). By analyzing satellite imagery data (DEM and Landsat 8 OLI), rainfall data, and administrative map of Pekanbaru City area with the help of GIS technology, the results of the analysis of these two parameters indicate that the city of Pekanbaru has a weighted average score is 2.70, so that the city of Pekanbaru has a severe impact categories rather prone to flooding inundation. The weighted scores of the two parameters in the city of Pekanbaru has shown that the land (weighted score of 1.33), the availability of water building (weighted score of 2.25), and the use of land (weighted score of 1.20) has a considerable influence on the cause of the flood puddles in the city of PekanbaruKeywords: inundation flood, GIS, parameters of flood, vulnerability